A toponímia urbana: uma proposta de sequência didática para o estudo do lugar no ensino de Geografia - Pereira, Erielson Miranda (2021)
The act of naming places is part of human existence. The symbolism of naming places presents itself as a geographical way of becoming unique in the occupation of a given place. The name of a place does not represent one name or another. Every name preserves a motive, a toponymic motivation. In this context, toponymic studies linked to the teaching of Geography with regard to the concept of place is an interdisciplinary, innovative and creative pedagogical proposal, not that it has not yet been applied. The main objective of this product is to provide a Pedagogical Sequence for teaching the place from a toponymic analysis - study of the proper names of places, and the specific objectives are: to discuss the teaching of toponymy from the national guidelines for basic education, highlighting its relevance in the context of School Geography and building a Pedagogical Sequence for teaching toponymy with didactic guidelines for Basic Education teachers. Methodologically, a bibliographical research was carried out in works that address the concept of place, its approach in School Geography, productions contribute to toponymic studies and product construction. The field of application took place at the Anjo da Guarda High School, a school located in the neighborhood of the same name in the city of São Luís – MA. The application took place through a Pedagogical Sequence, aiming at teaching the concept of place through an approach to the toponyms of the students' experience – the street where they live. It was found that the application of this proposal for the Teaching of Place through Toponyms allows for School Geography an opportunity to be followed and adapted for the use of toponymy in the classroom, in addition to enhancing a more critical reflection of students.